(U+5)(u+5)=

Simple and best practice solution for (U+5)(u+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (U+5)(u+5)= equation:


Simplifying
(U + 5)(u + 5) = 0

Reorder the terms:
(5 + U)(u + 5) = 0

Reorder the terms:
(5 + U)(5 + u) = 0

Multiply (5 + U) * (5 + u)
(5(5 + u) + U(5 + u)) = 0
((5 * 5 + u * 5) + U(5 + u)) = 0
((25 + 5u) + U(5 + u)) = 0
(25 + 5u + (5 * U + u * U)) = 0
(25 + 5u + (5U + uU)) = 0

Reorder the terms:
(25 + 5U + 5u + uU) = 0
(25 + 5U + 5u + uU) = 0

Solving
25 + 5U + 5u + uU = 0

Solving for variable 'U'.

Move all terms containing U to the left, all other terms to the right.

Add '-25' to each side of the equation.
25 + 5U + 5u + -25 + uU = 0 + -25

Reorder the terms:
25 + -25 + 5U + 5u + uU = 0 + -25

Combine like terms: 25 + -25 = 0
0 + 5U + 5u + uU = 0 + -25
5U + 5u + uU = 0 + -25

Combine like terms: 0 + -25 = -25
5U + 5u + uU = -25

Add '-5u' to each side of the equation.
5U + 5u + -5u + uU = -25 + -5u

Combine like terms: 5u + -5u = 0
5U + 0 + uU = -25 + -5u
5U + uU = -25 + -5u

Reorder the terms:
25 + 5U + 5u + uU = -25 + -5u + 25 + 5u

Reorder the terms:
25 + 5U + 5u + uU = -25 + 25 + -5u + 5u

Combine like terms: -25 + 25 = 0
25 + 5U + 5u + uU = 0 + -5u + 5u
25 + 5U + 5u + uU = -5u + 5u

Combine like terms: -5u + 5u = 0
25 + 5U + 5u + uU = 0

The solution to this equation could not be determined.

See similar equations:

| 4t+5=6t-17 | | 3(5x+4)/2=7x-8 | | 3.3=x+0.4 | | 0=5x^3-9x^2-6x+8 | | 0=3x^2-10x-349 | | 2/5(x-6)~x-1 | | (2t-8)/(t^2-16) | | 6y-3(y-5)=10 | | 7x+2x-9=5x+23 | | X=825+0.04x | | 7=7/9y= | | y=40(1/2)^(t/40) | | (7r+2)-5(r+3)=11 | | 2x+16+4x-12=180 | | 4x+9+7x-18=180 | | 8x-4+5x+20=180 | | (6/x)-(2/3)=-4/x | | 2(X+50)-3*(50-X)=5 | | 2(X+10)-3*(10-X)=5 | | 4x-12+x+17+2x=180 | | 2(X+35)-3*(35-X)=5 | | 2(X+55)-3*(55-X)=5 | | -2(4t-6)=5(3t-2) | | 4N=36*-2 | | (x-7)(x-7)=x^2+k(x)+m | | 2(X+20)-3*(20-X)=5 | | 2(X+100)-3*(100-X)=5 | | 3(2v+3)=-3(-3v+4) | | 2(X+15)-3*(15-X)=5 | | 4N=36(-2+N) | | 65+70+x+56=180 | | 2(X+5)-3*(5-X)=5 |

Equations solver categories